1999
DOI: 10.1159/000045244
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Morphometrical Interrelationships in Patients with Overt Nephropathy Induced by Non-Insulin-Dependent Diabetes mellitus

Abstract: To clarify the relationships between clinical and renal structural findings in non-insulin-dependent diabetes mellitus (NIDDM), we studied 19 renal biopsy specimens from patients with overt diabetic nephropathy induced by NIDDM. By a conventional biopsy examination using light, immunofluorescent and electron microscopy, we excluded patients with any non-diabetic renal diseases which may have caused urinary abnormalities. Using standard stereological methods, the glomerular filtration surface area per nephron (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The cell number in each glomerulus (n = 50) was calculated using preparations stained with hematoxylin and eosin. Glomerular sclerotic index was calculated as the percent of the PAS-positive area in the glomerular area in preparations stained with PAS [27] .…”
Section: Histological Examinationmentioning
confidence: 99%
“…The cell number in each glomerulus (n = 50) was calculated using preparations stained with hematoxylin and eosin. Glomerular sclerotic index was calculated as the percent of the PAS-positive area in the glomerular area in preparations stained with PAS [27] .…”
Section: Histological Examinationmentioning
confidence: 99%
“…Several studies have shown cross-sectional relationships between histological and clinical findings in diabetes type 1 or type 2 patients with nephropathy. [1][2][3][4][5] Studies by serial biopsies have also shown a relationship between changes in histological findings and the clinical course in these patients. [6][7][8][9] Although some longitudinal studies have demonstrated an association between the severity of global histological change and renal prognosis, 10,11 the specific morphological features predicting renal prognosis have only been described in a limited number of studies.…”
mentioning
confidence: 99%
“…These changes include increased glomerular filtration rate (GFR) and albuminuria after physical exercise, which may be more prevalent in cases of poor diabetes control. The changes determined by kidney biopsy, which were initially reported by Osterby and co-workers and later confirmed by other groups, include thickening of the glomerular basement membrane and mesangial expansion; the latter is considered to be the hallmark of early diabetic nephropathy [65][66][67][68][69][70]. Albeit of great pathophysiological interest, these findings are of limited clinical use for the following reasons (as also stated in the original report):…”
Section: The Profile Of Diabetic Nephropathy In Type 1 Diabetic Patientsmentioning
confidence: 96%